Serum Lipid Profile in Sheep Fed Diet Incorporated with Feed Additives - Beigh, Yasir A; Ganai, Abdul M; Muzamil, Showkeen; Mir, Danish; Ahmad, Haidar A; Mir, Shahid H (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A feeding trial to study the supplementation effect of exogenous fibrolytic enzymes (EFE) cocktail and wormwood herb on serum lipidprofile was conducted for 90 days in twenty crossbred lambs that were divided into four equal groups viz. T0 (Control) and T1, T2 and T3(treatment groups). T0 received total mixed diet (TMR) without any supplementation, while in treatments groups TMR was supplementedeither with EFE cocktail alone @ 0.60% (T1) or wormwood herb alone @ 4.50% (T2) and in a combination of the two feed additives (T3).At the end of the feeding trial, 6 days of digestibility trial was carried out to assess the supplementation effect in vivo on nutritionalparameters and serum total lipids and different lipoprotein fractions were carried out at the start (0 d) and subsequently at monthlyintervals of the experiment (30, 60 and 90 d). Nutrient digestibility, content as well intake were significantly higher in groups fed dietssupplemented with the feed additives either alone (p
Keywords: : Exogenous enzymes; Herb; Lipid; Sheep; Total mixed diet.